Математична модель ситуаційного синтезу автоматизованої системи збирання і оброблення інформації від технічних засобів моніторингу - Pysarchuk, Oleksii Oleksandrovych; Humeniuk, Maksym Oleksiiovych; Tymchuk, Serhii Vitaliiovych (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2017)
The problem was considered of increasing the efficiency of the automated system for collecting and processing information from the technical means of monitoring. The usage of situational synthesis system was proposed as a possible solution to this problem. Particular criteria of the optimal structure of the automated system for collecting and processing information were formulated. On the basis of the discrete convolution of partial criteria, a mathematical model of the situational synthesis system was developed. The entropy approach was applied to determine the necessary amount of technical means for monitoring. Technical means of monitoring were divided into classes and the informational content for each class was evaluated. The application of the complex mathematical model of the situational synthesis using given indicators allows to optimally choose means of monitoring that will be involved in the execution of the current job of the system.